Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Direktorat Perlindungan Perkebunan : The Influence of Work Environment and Work Motivation on the Performance of Employees of the Plantation Protection Directorate - Afriyanti Afriyanti; Murniyati Murniyati (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze how much influence the Work Environment partially has on Employee Performance, to analyze how much influence Work Motivation partially has on Employee Performance and to analyze how much influence the Work Environment and Work Motivation have a simultaneous effect on Employee Performance, this study uses a quantitative method because the research data is in the form of numbers and the analysis uses statistics. The number of samples in this study used saturated sampling, the sampling technique of which all members of the population were used as samples, this study consisted of 46 employees. Data collection techniques were carried out using questionnaires and observations. Based on the results of partial testing of the Work Environment on Employee Performance, the t-value was 1.363 <2.017 (ttable) and had a significant number of 0.180> 0.05. Based on the decision- making criteria, it can be concluded that H1 is rejected, this indicates that there is no positive and significant influence between Work Environment and Employee Performance. And based on the partial test results of Work Motivation on Employee Performance, the calculated t value is 3.531> 2.017 (t table) and has a significant number of 0.01 <0.05. Based on the decision-making criteria, it can be concluded that H2 is accepted, this indicates that there is a positive and significant influence between Work Motivation and Employee Performance. While based on the calculation results in table IV.16, the calculated F test results obtained are 34.246 when compared to the F table (alpha = 0.05 df = 3.21), then the f table value is 3.21 with a significant value of 0.05. So that the calculated F value > F table (34.246 > 3.21) and significance (0.001 < 0.05) then there is a positive and significant influence between the Work Environment and Work Motivation Simultaneously on Employee Performance